2016
DOI: 10.3390/ijerph13080808
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pre-Diabetes and Its Associated Risk Factors in Rural Areas of Ningbo, China

Abstract: Objective: The aims of the study were to investigate the prevalence of pre-diabetes and explore its associated risk factors in rural areas of Ningbo, China. Methods: A cross-sectional survey was conducted with 4583 adult residents in rural areas of Ningbo, China between March and May 2013. The survey used a multi-stage, stratified, cluster sampling method. Data collected included demographics and medical history, anthropometric measurements, blood pressure, blood lipid, and plasma glucose. After at least 10 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
24
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 32 publications
9
24
1
1
Order By: Relevance
“…14 Two large-scale national surveys conducted in China in the year 2007 and 2010 revealed that the prevalence of prediabetes increased from 16.0% to 50.9% in rural areas. 15 The prevalence of prediabetes in the present study is thus comparable to data from other parts of the country and other countries of the region. The findings of this study are a clarion call to the preventive health system to vigorously spread the message of preventing diabetes by adopting healthy active life style.…”
Section: Discussionsupporting
confidence: 88%
“…14 Two large-scale national surveys conducted in China in the year 2007 and 2010 revealed that the prevalence of prediabetes increased from 16.0% to 50.9% in rural areas. 15 The prevalence of prediabetes in the present study is thus comparable to data from other parts of the country and other countries of the region. The findings of this study are a clarion call to the preventive health system to vigorously spread the message of preventing diabetes by adopting healthy active life style.…”
Section: Discussionsupporting
confidence: 88%
“…The current study finding that abdominal obesity, family history of diabetes and being hypertensive were significant associated factors for diabetes has a sound basis in literature [44]. Not only do these factors independently increase the risk of diabetes, there have been suggestions that interaction between these factors further potentiate the risk of diabetes.…”
Section: Associated Factors For Diabetessupporting
confidence: 60%
“…Despite the fact that the study was carried out among inpatients, some findings could be cautiously extrapolated to the outpatients as well. Not unexpected with our understanding of disease status in rural and urban populations [1,19,21], patients' characteristics from two hospitals showed significant differences. Patients from SMH were older and less educated.…”
Section: Discussionmentioning
confidence: 95%
“…One major challenge in Chinese diabetes management derives from it diverse demographics and imbalanced distribution of medical service [18]. Even within the same administrative region the urban areas and the rural areas could show great differences in disease awareness, treatment and control [19]. The promotion of hierarchical diabetes treatment is one measure taken by Chinese government to improve this situation [18].…”
Section: Introductionmentioning
confidence: 99%